2019
DOI: 10.2196/10265
|View full text |Cite
|
Sign up to set email alerts
|

Weight Management in Young Adults: Systematic Review of Electronic Health Intervention Components and Outcomes

Abstract: Background Young adulthood is a vulnerable period for unhealthy lifestyle adoption and excess weight gain. Scant attention has been focused on developing and evaluating effective weight gain prevention strategies for this age group. Electronic health (eHealth) offers potential as a cost-effective means of delivering convenient, individually-tailored, and contextually-meaningful interventions at scale. Objective The primary aim of this systematic review was to locate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 107 publications
(343 reference statements)
2
56
0
Order By: Relevance
“…For example, in a review of 21 weight gain prevention randomised controlled trials (RCTs) in young adults, significant changes in weight and/or body mass index (BMI) were reported for half of the studies, more commonly those with a theoretical underpinning [14]. Further, in a recent review of eHealth weight management interventions for young adults, eight of 24 studies were found to have positive weight-related outcomes, most commonly web-based and multicomponent intervention approaches [12]. While the reviews to date provide important insight into effective intervention approaches for improving young adults' health behaviours, it is not yet clear which approaches are most effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a review of 21 weight gain prevention randomised controlled trials (RCTs) in young adults, significant changes in weight and/or body mass index (BMI) were reported for half of the studies, more commonly those with a theoretical underpinning [14]. Further, in a recent review of eHealth weight management interventions for young adults, eight of 24 studies were found to have positive weight-related outcomes, most commonly web-based and multicomponent intervention approaches [12]. While the reviews to date provide important insight into effective intervention approaches for improving young adults' health behaviours, it is not yet clear which approaches are most effective.…”
Section: Introductionmentioning
confidence: 99%
“…To synthesise the evidence for effective interventions targeting nutrition, physical activity and/or obesity for young adults, several systematic reviews have been conducted [ 12 15 ]. For example, in a review of 21 weight gain prevention randomised controlled trials (RCTs) in young adults, significant changes in weight and/or body mass index (BMI) were reported for half of the studies, more commonly those with a theoretical underpinning [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of these self‐regulation strategies are comparable to a systematic review of 24 e Health interventions in young adults, which reported self‐regulation skills (goal setting and self‐monitoring) as key strategies for weight management. Notably, all studies in that review which had positive weight‐related outcomes implemented some form of self‐monitoring . Goal setting requires the participant to set or agree on a goal defined in terms of a positive outcome of wanted behaviour, while self‐monitoring requires deliberate attention to the participant's own actions, as well as the conditions under which they occur, and their immediate and long‐term effects .…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been a sharp increase in interventions to prevent weight gain and/or initiate weight loss among young adults since the most recent systematic reviews on weight gain prevention (end search date: June 2014) and weight reduction in this group (end search date: March 2008) . In particular, there has been a substantial increase in electronic health (eHealth) interventions (defined as use of information and communication technologies for health) in the last decade . For example, this includes the consortium of seven Early Adult Reduction of weight through LifestYle intervention (EARLY) trials from the United States .…”
Section: Introductionmentioning
confidence: 99%
“…Reviews in young adults have not reported such strong supportive findings. Willmott et al 9 found a limited evidence base for eHealth weight management interventions targeting young adults but this was largely due to weak study designs.…”
Section: Introductionmentioning
confidence: 99%